PS01.061: LAPAROSCOPIC ENDOSTIM PLACEMENT: CASE REPORT. (14th September 2018) - Morales Morales, Carlos; Aguirre Mar, David; Ballí, Jorge; Serrano, Berta
Abstract: Background: GERD is a mechanical disorder that is caused by a dysfunction of the LES, dysfunction of the gastric emptying or an anomalous esophageal peristalsis. Methods: We present the case of a 36-year-old male patient with intermittent heartburn, regurgitation, retrosternal pain and dysphagia. UE reports grade D esophagitis, manometry and pHmetry reporting DeMeester 21.1, acid percentage of 5.8%. Normal Motility and LES in 9 mmHg. Nissen-type fundoplication was performed without complications and with resolution of symptoms. 4 years later the patient begins with recurrent symptoms. Esophagitis in UE. DeMeester 20. EEI 7.7 mmHg. 80% Useful Motility. Nissen type fundoplication is redo. Nine years later the patient starts again with symptoms. Progressive deterioration of esophageal motility in manometry is documented. UE with grade D esophagitis, DeMeester 10, manometry reporting LES with normal resting pressure and coordinated relaxation with pharyngeal contraction. Peristalsis wave failure of 100% of swallows, in relation to absent peristalsis; Results: Placement of Endostim was performed and patient was discharged without complications, Patient 1 month later without GERD symptoms. Conclusion: Approximately 10 to 40% of patients with GERD fail to respond in their symptomatology despite medical treatment. Surgical indications for GERD consist of failure to medical treatment, poor adherence to the patient's treatment, high volume reflux, severe esophagitis, benign stenosis and Barret's esophagus. Treatment consists of fundoplication in its different variants. However 10% to 20% of patients present with persistent symptoms and 3% to 5% require surgical reoperation. Endostim is a minimally invasive therapy which normalizes the function of the LES through neurostimulation. Disclosure: All authors have declared no conflicts of interest.